Analisis Investasi dan Kelayakan Ekonomi Penambangan Bentonit PT SMU di Desa Nangerang, Kecamatan Jampang Tengah, Kabupaten Sukabumi Provinsi Jawa Barat - Alifia Atsiila Fitri; Zaenal; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT SMU is a company that will plan bentonit mining in Nangerang Village, Jampang Tengah District, Sukabumi Regency, West Java Province which needs to be done investment analysis and economic feasibility of mine to see bentonit reserve prospect in that. To consider this, an economics analysis is required based on the concept of discounted cash flow analysis and sensitivity analysis. The parameters used to determine economic viability in bullion bentonit production of PT SMU are Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP) and sensitivity to NPV value due to changes in selling price and production cost. Based on analysis result of DCFROR analysis, Net Present Value value is Rp 20.386.301.635, Internal Rate of Return is 22,92 %, with Payback Period is 2,92 year, then this project is feasible to run. Then a sensitivity analysis is conducted to evaluate the impact of investment uncertainty by determining the level of profitability that will vary due to changes in sensitivity parameters. The parameters of investment that become the sensitivity parameter in this research are production cost and selling price. Assessment of sensitivity to NPV value due to changes in selling price and production cost at PT SMU assuming escalation of revenues and cost escalation by 3%. Net Present Value generated can show how sensitive the value obtained from the parameters of selling price. When the selling price drops above 12% and the production cost rises above more than 48%, then the project will be a loss. Keywords: Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PBP), Discounted Cash Flow (DCF), Sensitivity Analysis. Abstrak. PT SMU merupakan perusahaan yang melakukan penambangan bentonit di Desa Nangerang, Kecamatan Jampang Tengah, Kabupaten Sukabumi, Provinsi Jawa Barat. Sehingga perlu untuk dilakukan analisis investasi dan kelayakan ekonomi tambang untuk melihat prospek cadangan bentonit di lokasi tersebut. Untuk mempertimbangkan hal tersebut, maka diperlukannya analisis keekonomian berdasarkan konsep aliran kas diskonto (Discounted Cash Flow Rate of Return Analysis) dan analisis sensitivitas. Parameter yang digunakan untuk menentukan kelayakan ekonomi PT SMU adalah Net Present Value (NPV), Internal Rate of Return (IRR), Payback Periode (PBP) dan sensitivitas terhadap nilai NPV akibat perubahan harga jual dan biaya produksi. Berdasarkan hasil pengkajian analisis DCFROR didapat nilai Net Present Value yaitu Rp 20.386.301.635, Internal Rate of Return yaitu 22,92 %, dengan Payback Periode yaitu 2,92 tahun, maka proyek ini layak untuk dijalankan. Selanjutnya dilakukan Analisis sensitivitas untuk mengevaluasi dampak dari ketidakpastian investasi dengan menentukan tingkat profitabilitas yang akan bervariasi akibat perubahan parameter sensitivitas. Parameter investasi yang menjadi parameter sensitivitas pada penelitian ini yaitu biaya produksi dan harga jual. Penilaian sensitivitas terhadap nilai NPV akibat perubahan harga jual dan biaya produksi di PT SMU dengan asumsi eskalasi pendapatan sebesar 3%. Sehingga nilai Net Present Value yang dihasilkan dapat menunjukan seberapa sensitif nilai yang didapatkan dari parameter harga jual. Ketika harga jual menurun diatas 12% dan biaya produksi naik diatas lebih dari 48%, maka proyek ini akan rugi. Kata Kunci : Net Present Value (NPV), Internal Rate of Return (IRR), Payback Periode (PBP), Discounted Cash Flow (DCF), Analisis Sensitivitas